2015
DOI: 10.1111/1471-0528.13431
|View full text |Cite
|
Sign up to set email alerts
|

Manual perineal support at the time of childbirth: a systematic review and meta‐analysis

Abstract: Background Genital tract trauma is common with vaginal births and is associated with significant morbidity, particularly with obstetric anal sphincter injuries (OASIS). Debate continues regarding the effectiveness of perineal support during childbirth in reducing the risk of trauma.Objectives This review aimed to assess the effect of routine 'hands on'/manual perineal support (MPS) during childbirth, versus ad hoc/no perineal support ('hands off/poised'), on the risk and degree of perineal trauma.Search strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 53 publications
3
60
0
15
Order By: Relevance
“…Nevertheless, it is important to recognize that most of the randomized controlled trials (RCTs) that have evaluated the topic do not provide details about the technique used for perineal support or measures taken to ensure its standardization. Indeed, this is one of the major shortfalls of such RCTs compared with non‐randomized observational studies . Moreover, there is evidence from biomechanical studies that the accuracy of the performance of the different maneuvers, dependent on the type of MPP technique, is essential for its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is important to recognize that most of the randomized controlled trials (RCTs) that have evaluated the topic do not provide details about the technique used for perineal support or measures taken to ensure its standardization. Indeed, this is one of the major shortfalls of such RCTs compared with non‐randomized observational studies . Moreover, there is evidence from biomechanical studies that the accuracy of the performance of the different maneuvers, dependent on the type of MPP technique, is essential for its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Raisanen et al 9 hypothesized that the increased severe perineal trauma risk is because of fetopelvic disproportion which also predisposes a primary cesarean delivery. 17 Episiotomy is the most commonly performed obstetric procedure and was traditionally thought to decrease the risk of major perineal trauma and pelvic floor dysfunction in later life. Hehir et al 10 reported that "a large number" of women with severe perineal trauma in a subsequent vaginal delivery had progressed to an advanced stage before delivering by primary cesarean section (n = 27/60).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Careful clinical assessments, taking in a wide spectrum in routine clinical work, are nonetheless a valuable addition to the evidence and can shift emphasis toward methods that strive to improve health outcomes. 7,8 Careful clinical assessments, taking in a wide spectrum in routine clinical work, are nonetheless a valuable addition to the evidence and can shift emphasis toward methods that strive to improve health outcomes.…”
Section: Discussionmentioning
confidence: 99%